A modification of the convergence conditions for Picard's iteration - Ezquerro,J. A. (2004)
The convergence of the method of successive approximations is usually studied by the fixed point theorem. An alternative to this theorem is given in this work, where a contraction mapping is not necessary. An application to nonlinear integral equations of Fredholm type and second kind is also presented.